(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Alinsug MV, Estandarte MHG, Somodio EMN, Sabarita MJJ, Deocaris CC. 2021. Biodiversity of ethnomedicinal plants from the B’laan Tribe in Mount Matutum Protected Landscape, Southern Mindanao, Philippines. Biodiversitas 23: 554-563. Mount Matutum Protected Landscape (MMPL) is one of the key biodiversity areas in Mindanao Island, Philippines, and is part of the ancestral domains of 18 indigenous peoples. The present study aims to establish a comprehensive inventory of the medicinal flora at MMPL according to the traditional healing practices of the B’laan, a tribal community whose cultural heritage is anchored to their interactions with nature and with a rich and understudied ethnomedicinal system. Focus group discussions and key informant interviews of the tribal healers from five tribal communities revealed 101 medicinal plants belonging to 33 families were identified. The plant species have therapeutic uses for 19 disease categories. Roots and leaves are the most utilized parts which are made into a decoction, the most common preparation for oral intake. Tawal-ulad (Lunasia amara Blanco), which is used as a treatment for snake bites, dengue, dysmenorrhea, constipation, rabies, and hypertension has the highest use value (UV). Informant Consensus Factor (ICF) analysis revealed that cholera, scabies, viral infections, warts, beriberi, diabetes, gastric ulcer are the most common diseases treated with medicinal plants by the B’laan tribal healers. The biodiversity of medicinal plants, although some remain unidentified at the species level, reflects the centuries-old ethnomedicinal knowledge of the B’laan Tribe. Our study is the first comprehensive documentation of the ethnomedicinal knowledge of the B’laan Tribe residing at MMPL.